2022
DOI: 10.1051/0004-6361/202141037
|View full text |Cite
|
Sign up to set email alerts
|

The observed multiplicity properties of B-type stars in the Galactic young open cluster NGC 6231

Abstract: Context. It is well known that massive O stars are frequently (if not always) found in binary or higher-order multiple systems, but this fact has been less robustly investigated for the lower mass range of the massive stars, represented by B-type stars. Obtaining the binary fraction and orbital parameter distributions of B-type stars is crucial to understand the impact of multiplicity on the archetypal progenitor of core-collapse supernovae as well as to properly investigate formation channels for gravitationa… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
29
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
3
1

Relationship

1
7

Authors

Journals

citations
Cited by 46 publications
(39 citation statements)
references
References 63 publications
3
29
1
1
Order By: Relevance
“…This unfortunate alignment of cadence and orbital phase explains why our data do not reveal its multiplicity. Including these two literature binaries would raise the raw (uncorrected for line profile variability contamination) multiplicity fraction of our GOSC sample to 16 out of 25 sources-64%-comparable to multiplicity fractions of other OB star samples (Kobulnicky et al 2014;Banyard et al 2022). Our data reinforce the conclusion that multiple-star systems are common, not just among OB stars in general, but among high-velocity runaways as well.…”
Section: Multiplicity Fraction Of Runaway Gosc Starssupporting
confidence: 74%
See 2 more Smart Citations
“…This unfortunate alignment of cadence and orbital phase explains why our data do not reveal its multiplicity. Including these two literature binaries would raise the raw (uncorrected for line profile variability contamination) multiplicity fraction of our GOSC sample to 16 out of 25 sources-64%-comparable to multiplicity fractions of other OB star samples (Kobulnicky et al 2014;Banyard et al 2022). Our data reinforce the conclusion that multiple-star systems are common, not just among OB stars in general, but among high-velocity runaways as well.…”
Section: Multiplicity Fraction Of Runaway Gosc Starssupporting
confidence: 74%
“…These results show that both the full OB-star SBN sample and O-star SBN sample are consistent with the runaway GOSC O-star multiplicity fraction within 1σ. The apparent multiplicity fraction of the GOSC and SBN samples are formally consistent, despite the fact that early B stars dominate the SBN sample , and B stars have been shown to exhibit a lower multiplicity fraction than O stars (Kobulnicky et al 2014;Banyard et al 2022). This bias should augment the disparity in spectral type between the samples.…”
Section: Multiplicity Fraction Of Runaway Gosc Starsmentioning
confidence: 65%
See 1 more Smart Citation
“…The spectroscopic binary fraction reaches ∼50% for B stars and up to ∼70% for O stars, meaning that long-period massive binaries also exist. Indeed, the period distribution of massive binaries with ages of a few megayears follows a well-defined power law, ranging from about 1 d to at least 10 years (Fryer et al 2012;Sana et al 2012Sana et al , 2014Kobulnicky et al 2014;Almeida et al 2015;Banyard et al 2021;Villaseñor et al 2021). A migration affecting about half to two-thirds of all OB stars is therefore probably sufficient to explain the wide variety of separation observed.…”
Section: Connection With Star Formation Modelsmentioning
confidence: 98%
“…Geller et al ( 2021 ) summarized their observations of o v er 45 yr for the old OC M67 and reported an o v erall α = 34 ± 3 per cent and 70 ± 17 per cent for the cluster centre. On the other hand, Banyard et al ( 2022 ) estimated α to be 52 ± 8 per cent for the B-type stars of the OC NGC 6231.…”
mentioning
confidence: 96%